1997
DOI: 10.1038/sj.cdd.4400235
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in the gastrulating chick embryo: potential roles for tumor necrosis factor-alpha (TNF-α)

Abstract: We have examined the expression of TNF-alpha and its receptors, TNFR1 and TNFR2, during gastrulation in the chick embryo, and have investigated the possible role of this factor in the control of cell death at this early stage of development. TNF-alpha, immunoreactive at approximately 17 kD, was found both in vivo and in vitro, most intensely associated with the cell surface and cytoskeleton of endoderm cells. TNFR2 was especially immunoreactive in endoderm cells of the marginal zone. TNFR1 was found in nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(84 reference statements)
0
5
0
1
Order By: Relevance
“…As the neural plate arises, TUNEL-positive cells accumulate at the edge of the Dad1-expressing domain, forming an arc at the border of the neural plate (future neural crest and placode area) and proximal non-neural ectoderm. These regions retain a higher incidence of apoptosis at later stages of development (Graham et al, 1993, Hensey and Gautier, 1998, Sanders et al, 1997a, Sanders et al, 1997b, Wride et al, 1994. In our experiments, misexpression of DAD1 at the edges of the neural plate causes a small reduction in the incidence of PCD compared to electroporated controls in some embryos, but this is quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…As the neural plate arises, TUNEL-positive cells accumulate at the edge of the Dad1-expressing domain, forming an arc at the border of the neural plate (future neural crest and placode area) and proximal non-neural ectoderm. These regions retain a higher incidence of apoptosis at later stages of development (Graham et al, 1993, Hensey and Gautier, 1998, Sanders et al, 1997a, Sanders et al, 1997b, Wride et al, 1994. In our experiments, misexpression of DAD1 at the edges of the neural plate causes a small reduction in the incidence of PCD compared to electroporated controls in some embryos, but this is quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…The early chick and mouse embryos also show cell death, often with apoptotic morphology, during gastrulation (Jacobson 1938;Bellairs 1961;Daniel and Olson 1966;Sanders et al 1997); neural tube closure (Schlüter 1973;Geelen and Langman 1977); neural crest formation (Vermeij-Keers and Poelmann 1980;Lumsden et al 1991;Homma et al 1994), and among the primordial germ cells (Coucouvanis et al 1993;Pesce and De Felici 1994). In the mouse, cell death has been described both in the ectoderm (Poelmann and Vermeij-Keers 1976;Poelmann 1980;Chen et al 1994) and in the visceral endoderm from the mid-streak stage onwards (Lawson et al 1986;Lawson and Pederson 1987), but its significance has been enigmatic.…”
Section: Introductionmentioning
confidence: 98%
“…Although the mechanisms of protection against apoptosis by bcl-2 are not fully understood, it apparently plays a role in the regulation of pore opening of mitochondria (Zamzami et al, 1996), and in protection against oxidative damage (Hockenbery et al, 1993). Using immunohistochemistry, Sanders et al (1997b) found that bcl-2 was distributed throughout the gastrulating (stage 4) chick embryo. In the present study, we found that bcl-2 is expressed at earlier developmental stages as well.…”
Section: Blastodermal Cells Demonstrate Resistance To Temperature Shocksmentioning
confidence: 99%
“…Bcl-2, sharing sequence and functional similarities with ced-9, has been detected as early as stage E8.5 in mouse embryos and by E10.5 is prominent in the immature neural tissue of the brain and spinal cord (Novak and Korsmeyer, 1994). More recently, the bcl-2 and bax proteins were detected in sections of stage 4-5 (gastrulation) chick embryos immunostained for these antigens (Sanders et al, 1997b). Although c-myc is expressed in all proliferating cells, and promotes apoptosis under certain circumstances, its role as a potential cell death regulatory gene in pre-gastrulating embryos has not been explored.…”
Section: Introductionmentioning
confidence: 99%